Knowledge and beliefs of endocrine disruptors in pediatrics: all hands on deck! - Portefaix, Aurélie; Loppinet, Thomas; Tourvieilhe, Laura; Balice, Giuseppe; de Veron de La Combe, Nathan; Kassai, Behrouz; Bacchetta, Justine (Frontiers in Public Health, 2024)
Please find enclosed our revised manuscript reporting the results of the STENDAL study, entitled: "Knowledge and beliefs of endocrine disruptors in paediatrics: all hands on deck!" which we are submitting for publication as a Brief Report in Frontiers Public Health, after our modifications in response of the both reviews done.Our study focused on endocrine disruptor knowledge and beliefs of parents as well as pediatric health professionals. Endocrine disruptors (EDs) are an increasing concern for parents and pediatricians. Their roles in the development of chronic diseases are increasingly being questioned.They are ubiquitous in our daily lives, and we need to inform adequately our patients and their parents on their potential risk.The aim of our survey was to simultaneously assess the knowledge of parents and professionals on EDs, using a simple questionnaire. We received a high number of responses from parents and pediatric professionals indicating their interest in the subject. Correct responses to our survey from health professionals were higher than those from parents (73% vs. 60%). However, even though 66 % of parents and 95 % of professionals had already heard about EDs, only 10 % and 5 % felt sufficiently informed, respectively. Information sources were similar media (television or radio) and the Internet in both groups.Research on environmental exposure is a new domain for pediatricians and informing families is a crucial issue. We believe that our results can be of interest for the pediatric community.